Identifying the abilities of biostimulants to improve vegetable production compared with conventional fertilizer - Raza, Qurat-Ul-Ain; Rehim, Abdur; Bashir, Muhammad Amjad; Raza, Hafiz Muhammad Ali; Aon, Muhammad; Geng, Yucong; Moustafa, Mahmoud; Alshaharni, Mohammed O.; Ali, Haider; Lucas, Rosa Sanchez (Frontiers in Sustainable Food Systems, 2024)
Vegetables are important agricultural products with numerous health benefits. Excessive chemical fertilization to meet the food challenge has resulted in environmental and soil health hazards. Considering this aspect, the current study was conducted with the aim to introduce biostimulants as an alternative to chemical fertilizers to improve soil quality, crop quality, and yield. In the first experiment, the response of radish was noted against the application of glycine (GLY), aspartic acid (ASP), lysine (LYS), vitamin B complex (VBC), and chemical fertilizers (CF). The biostimulants were sourced from Sigma Aldrich and Martin Dow Market Ltd. The results indicated that ASP has significantly improved the phenolic contents in shoot (1.01%) and root (12.23%) compared with CF. Additionally, total protein was significantly increased in shoot with GLY (251.81%) and in root with ASP (57.06%). Shoot ascorbic acid contents were significantly improved with ASP (179.90%), VBC (159.91%), and LYS (139.92%). Plant fresh and dry weight was improved with VBC (478.31%) and ASP (364.73%). The N and P concentrations in radish root were higher in VBC (25.93%) and LYS (100%). Soil organic matter was improved ASP (61.51%), followed by VBC (60.13%). Soil available P concentration was also enhanced with LYS (40.43%), ASP (31.20%), and VBC (23.19%). The second experiment was focused on identifying the response of turnip crop against the following treatments: chemical fertilizers (CF), Isabion® (ISA), 25% CF + LYS + GLY (CLG), 25% CF + ASP + GLY (CAG), and 25% CF + ASP + LYS (CAL). The biostimulants were sourced from Sigma Aldrich Syngenta, Pakistan. The results denoted that CAL and ISA significantly improved the phenolic contents in turnip shoot and root. The ascorbic acid in turnip shoot was improved with CAL (19.27%), CAG (18.13%), ISA (17.68%), and in root with CLG (26.96%). The P concentration in turnip shoot was significantly higher in ISA (19.25%), CLG (16.85%), and CAG (12.26%). Soil total N was improved in all treatments. ISA improved the available P concentration, whereas CF (67.87 mg kg−1) followed by ISA (65.93 mg kg−1) improved the soil available K. Both studies conclude that biostimulants capable of improving vegetable quality.